The Relationship Between Player's Gaming Orientation and Avatar's Capital: a Study in Final Fantasy XIV - Henry Korkeila; Juho Hamari (Hawaii, USA, 2022)
This study investigates the relationship between player’s gaming orientation (dimensions of achievement, immersion and social orientation) and avatar’s capital (social, economic, cultural and symbolic). The data was gathered through an online survey (n=905) amidst players of a MMORPG, Final Fantasy XIV. The results show that avatar’s cultural capital is predicted by immersion orientation (customization, discovery, and role-playing), achievement orientation (mechanics) and social orientation (relationship and socializing). Economic capital is predicted by achievement orientation (advancement, competition, and mechanics) and social orientation (relationship and teamwork). Social capital was predicted by social orientation (relationship, socializing and teamwork) and immersion-orientation (escapism and customization). Symbolic capital was predicted by achievement orientation (advancement, competition, mechanics) and social orientation (relationship and teamwork).
Proceedings of the 51st Annual Hawaii International Conference on System Sciences